2019
DOI: 10.1088/2053-1591/ab5d7e
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical and impedance spectroscopy study of thin film of polyaniline (PANI/ZnO) nanocomposite

Abstract: Modern organic electronic and power electronic devices gained attention due their superior performance and efficiency with reduced cost. While nanocomposites of these organic semiconductors have high potential to further enhance these properties. In this work, thin films of zinc oxidepolyaniline (ZnO-PANI) nanocomposite with different compositions of ZnO (50, 60 and 70 wt%) are deposited by spin coater onto the surface of p-Si. The phase identification of the samples is identified through x-ray diffraction ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…However, as the voltage becomes positive, the impedance demonstrates an increasing trend correlated with the rise in voltage values, reaching a peak at 200 kHz. The Z ″ spectroscopic plot indicates a solitary relaxation event consistently occurring at a frequency of 200 kHz across all positive voltage values examined . Beyond this frequency, the impedance value decreases with the further increase in frequency.…”
Section: Resultsmentioning
confidence: 88%
“…However, as the voltage becomes positive, the impedance demonstrates an increasing trend correlated with the rise in voltage values, reaching a peak at 200 kHz. The Z ″ spectroscopic plot indicates a solitary relaxation event consistently occurring at a frequency of 200 kHz across all positive voltage values examined . Beyond this frequency, the impedance value decreases with the further increase in frequency.…”
Section: Resultsmentioning
confidence: 88%
“…It can be concluded that with the addition of Sr(NO 3 ) 2 , the disorder and relaxation time in the PANI increases, hence the carriers either can find different pathways for transport or get trapped in the inhomogeneity in the sample. [ 51 ]…”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that with the addition of Sr(NO 3 ) 2 , the disorder and relaxation time in the PANI increases, hence the carriers either can find different pathways for transport or get trapped in the inhomogeneity in the sample. [51] The parameters shown in Table 1 indicate that the depressed or skewed semicircle is because of spatial inhomogeneities in the samples. The parameters α1 and α2 that represent surface and bulk components show variation in their values.…”
Section: Complex Impedancementioning
confidence: 99%
“…XRD patterns of PANI-ZnO (10, 20, 30 wt.%) composites show higher crystallinity compared to PANI as the concentration of ZnO increases [30]. At the highest concentration of 30 wt.%, the diffraction pattern showed more peaks like ZnO, and the peaks shifted towards the lower angle side [31].…”
Section: Preparation Of Pani and Pani-zno Thin Lmsmentioning
confidence: 98%